(untitled) (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Rochaddi B, Zainuri M, Sabdono A. 2019. Short Communication: Diversity of Chlorpyrifos-degrading bacteria isolated from shallow aquifer of East Java Coastal Settlements, Indonesia. Biodiversitas 20: 3662-3666. Wastes from inhabited regions, factories and maricultural practices through movement and penetration enter to groundwaters. A study was undertaken to determine the diversity of Chlorpyrifos-degrading bacteria isolated from a shallow aquifer of East Java coastal settlements. Fifteen of 116 bacterial strains isolated from shallow aquifer samples of 12 household wells were selected due to their capability of degrading Chlorpyrifos herbicide. These isolates were different in the ability of Chlorpyrifos degradation. They utilize Chlorpyrifos as the source of carbon and energy for their growth. Their initial degradation at 50?mg?L?1 concentration within the first 4 days ranged between 26.81 and 70.12 %. The 16S rRNA gene sequence analyses indicated that the majority of the isolates belonged to members of Bacillus genera. These bacterial strains were Bacillus cereus (seven strains) and Bacillus paramycoides (four strains). Besides, three strains were identified as Bacillus subtilis and one strain as Bacillus thuringiensis. Bacillus cereus strain LCA1.1 was selected for further study on kinetic growth and Chlorpyrifos utilization. These bacterial strains have a great potential utility for the bioremediation of shallow aquifer of coastal settlement contaminated with Chlorpyrifos pesticides.